Customers Perception Study to Increase Brand Awareness in BJB Precious (The Indonesian Journal of Business Administration, 2021)
Bjb Precious the priority services owned by PT Bank Jawa Barat Banten (bjb). Although the number of customers is increasing every year, but it is not accompanied by the brand awareness of bjb Precious. To avoid language barriers for bjb Precious in the public, in 2021 bjb Precious will do a rebranding into bjb Prioritas so that it is better known to the public. With low brand awareness, bjb Precious will make some improvements after the rebranding. This research is intended to propose a marketing strategy to increase brand awareness of bjb Precious. In this study, identification was carried out internally and externally through the marketing mix (7P's), STP analysis, PESTEL analysis, competitor analysis, Porter's Five Forces analysis, and consumer analysis. In consumer analysis, this study uses a qualitative approach based on observations and interviews from several related parties. The interview was addressed to bjb Precious employees, bjb Precious customers, and priority customers in other banks. Interviews with customers were conducted to determine their perceptions of priority services and bjb Precious. From the interview results, there are several findings from this research, including priority customers from other banks who are not interested in using bjb Precious services, because they do not trust in bjb Precious. Besides that, they do not know about the products, facilities, or privileges provided by bjb Precious. Most of them do not know bjb Precious at all. Therefore, bjb Precious needs to build positive communication with the public on an ongoing basis. In addition to priority customers in other banks, customers from bjb Precious also provide their perceptions based on the marketing mix of bjb Precious. From these findings, several business solutions will be proposed, in terms of service improvements and how to communicate them to customers to increase brand awareness of bjb Precious.Keywords: bjb Precious, perception, brand awareness, marketing mix, marketing communication.